Microscopic origins of the induced X(2)in thermally poled phosphate glasses - P. Thamboon (2018)
We have investigated the microscopic origins of the induced X(2)in two phosphate glasses: a self-prepared lanthanum phosphate glass with molar composition 0.2La2O30.8P2O5and a commercial sodium alumino phosphate glass (IOG-1, Schott Glass Technologies, Inc.) with molar composition 0.6 P2O50.24Na2O 0.13 Al2O3 0.03Ce2O3. The drastic difference in alkali content in these two phosphate glass systems results in different origins of their induced X(2). For the poled lanthanum phosphate glass, the origin of the induced X(2), which is directly proportional to the dc field established inside the glass, is the result of charge migration. A model that uses a single-positive-charge carrier with a nonblocking cathode describes the anodic surface X(2)of 30 μm thickness. For the poled sodium alumino phosphate glass, two mechanisms-dipole reorientation via the applied field and charge migration-are responsible for the origin of the bulk and the surface X(2). Dipole reorientation via the applied field is suggested for the bulk contribution, while a charge migration model that involves multiple-charge carriers with nonblocking electrodes is appropriate for the surface X(2). © 2009 American Institute of Physics.